Reviewing Franchise Business Legal Regulations: A Perspective on Consumer Protection and Intellectual Property Rights Protection - Dimas Guntur Kencono (Proceeding International Conference Restructuring and Transforming Law, 2023)
This article discusses the legal perspective in franchise businesses. The franchise business has become a popular business model in Indonesia, however, this business model is not free from legal problems. The author discusses a strong legal foundation related to brand protection, franchise regulations, and its relationship to employment law. Apart from that, the author also discusses the franchise business model and the obligations that must be fulfilled by the franchisor and franchisee. The author believes that from a legal perspective, franchise businesses must comply with existing regulations, including brand protection and employment rights. Openness, transparency and balanced involvement between franchisors and franchisees also need to be emphasized. Therefore, parties involved in a franchise business must understand the applicable regulations and laws to avoid legal problems in the future.